Negative result: 6-(N,N-dimethylamino)fulvene as a reagent for the detection of latent fingermarks on paper surfaces - Wells, Jason; Parsons, Zachary; Jelly, Renee; Payne, Alan D.; Lewis, Simon (2019)
This is the first report of 6-(N,N-dimethylamino)fulvene (DMAF) as a reagent for the detection of latent fingermarks on porous surfaces. Through observation of undergraduate students showing poor laboratory hygiene, we noted that exposure to DMAF leads to brown staining on the students’ skin. Subsequently we found that it can develop latent fingermarks on paper surfaces as pale pink impressions, which are luminescent when illuminated at 505nm and viewed through orange goggles. Unfortunately the technique does not perform as well as currently available approaches, however it may be useful as “lead” compound for the synthesis of non-ninhydrin based fingermark reagents.